Malignant Mixed Epithelial and Stromal Tumor of the Kidney With 2 Simultaneous Renal Carcinomas in a Male Patient: Case Report and Review of the Literature. (February 2018) - Arriola, Aileen Grace P.; Taylor, Benjamin L.; Ma, Sophia; Malkowicz, S. Bruce; Lal, Priti
The majority of mixed epithelial and stromal tumors (MEST) of the kidney are benign entities found in female patients. Malignant MEST of the kidney is an extremely rare entity that often behaves clinically similar to an undifferentiated sarcoma. We report a case of a malignant MEST with synchronous papillary and clear cell renal cell carcinomas (RCCs) in a 61-year-old Caucasian man who presented with an incidental finding of a left renal mass on workup for back pain. The patient underwent a left radical nephrectomy, with histopathology confirming a malignant MEST, intimately associated papillary RCC, and separate adjacent focus of clear cell RCC.